Research progress on the antitumor effects of harmine - Hu, Yonghua; Yu, Xiaoli; Yang, Lei; Xue, Gaimei; Wei, Qinglin; Han, Zhijian; Chen, Hao (Frontiers in Oncology, 2024)
Harmine is a naturally occurring β-carboline alkaloid originally isolated from Peganum harmala. As a major active component, harmine exhibits a broad spectrum of pharmacological properties, particularly remarkable antitumor effects. Recent mechanistic studies have shown that harmine can inhibit cancer cell proliferation and metastasis through epithelial-to-mesenchymal transition, cell cycle regulation, angiogenesis, and the induction of tumor cell apoptosis. Furthermore, harmine reduces drug resistance when used in combination with chemotherapeutic drugs. Despite its remarkable antitumor activity, the application of harmine is limited by its poor solubility and toxic side effects, particularly neurotoxicity. Novel harmine derivatives have demonstrated strong clinical application prospects, but further validation based on drug activity, acute toxicity, and other aspects is necessary. Here, we present a review of recent research on the action mechanism of harmine in cancer treatment and the development of its derivatives, providing new insights into its potential clinical applications and strategies for mitigating its toxicity while enhancing its efficacy.